Facelift Techniques: An Overview - Kaya, Kerem Sami; Cakmak, Ozcan (Facial Plastic Surgery, 2022)
Facelift techniques can be classified according to the depth and extent of the dissection applied. Imbrication and plication of the superficial musculoaponeurotic system (SMAS) referred to as “SMAS lifts” or “classical facelifts” are the most commonly used techniques. Plication techniques involve in-folding of the SMAS and suture suspension without any SMAS incision whereas imbrication techniques involve a SMAS incision with a portion of the SMAS either removed or transposed with or without limited sub-SMAS dissection. Aging changes in the lower face and neck can be successfully treated with SMAS lift techniques. However, there is no lifting effect at midface level or improvement in the nasolabial folds since the retaining (zygomatic cutaneous and masseteric cutaneous) ligaments that prevent the transmission of traction to the malar portion of the facelift dissection are not released. Extended facelift techniques involve surgical release of these ligaments, and produce combined, balanced, and harmonious rejuvenation of the midface, cheek, and lower face without requiring a separate midface lift procedure. There are different techniques having similar extended midface dissections with some variations: The extended SMAS technique involves a long skin flap and a distinct SMAS flap dissected and pulled separately. The high SMAS technique has a similar dissection but involves a higher SMAS flap along the superior border of the zygomatic arch. The deep plane facelift involves undermining of skin-SMAS flap as a single unit following a more limited subcutaneous dissection. In the composite plane facelift, in addition to deep plane facelift dissection, the lower part of the orbicularis oculi muscle is also dissected and included in the flap. As they have a single unit, deep and composite flap facelifts allow excellent blood supply to the overlying skin. In this article, various facelift techniques are discussed in detail in line with the relevant surgical anatomy.
Keywords: facelift; rhytidectomy; SMAS lift; deep plane facelift; composite plane facelift